2014
DOI: 10.1586/14737175.2015.992415
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanisms and clinical applications of mild hypothermia and electroconvulsive therapy on refractory status epilepticus

Abstract: Status epilepticus (SE) is an acute and severe neurological disorder. A small number of SE cases cannot be terminated by a sufficient therapeutic dose and duration of two to three common anticonvulsant therapies. The continuing seizures often lead to poor prognosis and a higher mortality rate. Novel non-drug treatment options to terminate SE are greatly needed. Induced hypothermia and electroconvulsive therapies are used to treat SE. There are many case studies and multiple experimental investigations of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…The results also support studies which suggested that electroconvulsive therapy (ECT) which can increase hippocampal neurogenesis (Bouckaert et al, ; Madsen et al, ; Olesen, Wortwein, Folke, & Pakkenberg, ; Scott, Wojtowicz, & Burnham, ) also reduces seizure susceptibility in patients with epilepsy (Lunde, Lee, & Rasmussen, ; Yang & Wang, ). These findings are consistent with studies showing that P7C3, a drug that enhances adult hippocampal neurogenesis (Latchney, Jaramillo, Rivera, Eisch, & Powell, ; Pieper, McKnight, & Ready, ) is neuroprotective (Blaya, Bramlett, Naidoo, Pieper, & Dietrich, ; Tesla et al, ; Walker et al, ) and ameliorates cognitive impairments in a mouse model of Alzheimer's disease (Choi et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…The results also support studies which suggested that electroconvulsive therapy (ECT) which can increase hippocampal neurogenesis (Bouckaert et al, ; Madsen et al, ; Olesen, Wortwein, Folke, & Pakkenberg, ; Scott, Wojtowicz, & Burnham, ) also reduces seizure susceptibility in patients with epilepsy (Lunde, Lee, & Rasmussen, ; Yang & Wang, ). These findings are consistent with studies showing that P7C3, a drug that enhances adult hippocampal neurogenesis (Latchney, Jaramillo, Rivera, Eisch, & Powell, ; Pieper, McKnight, & Ready, ) is neuroprotective (Blaya, Bramlett, Naidoo, Pieper, & Dietrich, ; Tesla et al, ; Walker et al, ) and ameliorates cognitive impairments in a mouse model of Alzheimer's disease (Choi et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…Centromedian thalamic nuclei DBS was also used to resolve refractory SE in a 27-year-old man ((Valentín et al, 2012) and a 17-year-old boy (Lehtimäki et al, 2017). Furthermore, electroconvulsion therapy (ECT) is reported in patients with refractory SE, and SE cessation was obtained in 80% of cases, and complete recovery was achieved in 27% of patients (Lambrecq et al, 2012;Yang and Wang, 2015). The SANTE study demonstrated the efficacy of ANT-DBS in controlling seizures and improving patient quality of life based on prospective, controlled research and long-term follow-up (Salanova et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The definition of status epilepticus, proposed by the International League Against Epilepsy in 2001, is a seizure that lasts beyond the ordinary duration for a seizure of that type in most patients or repeats between which the function of CNS does not return to normal baseline [75]. Refractory status epilepticus is defined as failure of two to three common anticonvulsants, such as diazepam, phenobarbital, phenytoin, clonazepam and so on, to control the onset of status epilepticus with a sufficient therapeutic dose and duration or status epilepticus that lasts over an hour [75].…”
Section: Refractory Status Epilepticusmentioning
confidence: 99%
“…Refractory status epilepticus is defined as failure of two to three common anticonvulsants, such as diazepam, phenobarbital, phenytoin, clonazepam and so on, to control the onset of status epilepticus with a sufficient therapeutic dose and duration or status epilepticus that lasts over an hour [75]. Refractory status epilepticus is a lifethreatening condition that occurs in approximately 30% of patients with status epilepticus and is considered to be associated with increased functional disability and hospital length of stay [76].…”
Section: Refractory Status Epilepticusmentioning
confidence: 99%